Death at the edges of empire : fallen soldiers, cultural memory, and the making of an American nation, 1863-1921 - Bontrager, Shannon (Studies in war, society, and the military., 2020)
"Shannon Bontrager examines the culture of death, burial, and commemoration of fallen American soldiers in the Civil War, the Spanish-Cuban-American War, the Philippine-American War, and World War I. He links the cultural and political history of American war dead to explore the transatlantic and transpacific contexts of America's imperial ambitions"--